Organic memory and electrical bistability in a quinone –based charge transfer complex - Rath, Arup Kumar; Pal, Amlan J. (Proceedings of the IEEE, 2009)
We present an overview of the issues of organic memory devices and discuss the mechanisms involved in conductance switching. To make the memory elements addressable, we introduce nanostructures of a quinone-based charge-transfer complex. The devices based on charge-transfer complexes exhibit electrical bistability. Apart from characterizing complex formation, we study characteristics of memory devices based on the complexes. The mechanism of bistability has been discussed in terms of electroreduction of the quinone derivative with the formation of a percolating network of conducting molecules or channels across the device. Depending on the device architecture, a device may exhibit memoryswitching or threshold-switching phenomenon. The former system has displayed read-only and random-access memory applications.